ANALISIS KEGIATAN LITERASI DALAM MENUMBUHKAN SEMANGAT PESERTA DIDIK - Dewi Retno Iswarii; Sri Suneki; Sukamto; Maslinda (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
Literacy culture is not just an individual's hobby or preference in terms of reading, but rather an effort to meet the needs and challenges of the times. Literacy culture is important in creating an intelligent society, so that it will form a superior and quality nation. Through literacy activities, a person has the provision to face the challenges that exist today and the challenges that will come in the future. This is because literacy activities will affect one's mindset in reading existing situations and opportunities, so that a person will be more careful in making future decisions. Literacy culture needs to be carried out wherever and whenever. Schools in fostering students' enthusiasm for learning can be seen from how the literacy culture is carried out. This research was conducted at SD Sampang 02 using a descriptive qualitative approach with teachers and students as subjects. Data collection techniques used in this study were interviews, observation, and documentation. Techniques to test the validity of the data using triangulation techniques. SDN Sampangan 02 implements a literacy culture with new innovations, literacy activities at SDN Sampangan 02 are called Acikamen which means I Read You Listen. Acikamen activities are carried out in the school yard by all students. This activity not only guides students to read books, but also channel their interests and talents. Through this Acikamen literacy activity it is hoped that students will be more enthusiastic about learning.